J. M. Keynes and the Postwar International Economic Order - Newton, Scott (History compass, 2006)
Keynes was at the heart of efforts to establish a reformed international economy after World War Two. But the outcome of his efforts left him a disappointed man. Although the postwar international economic architecture owed much to Keynes it fell short of his ideals. It is arguable that international politics had as much to do with the era of expansion as the Bretton Woods institutions, and that even today the world has not yet grasped the full extent of the Keynesian challenge.